Female Physicists in Ugandan Universities - D’ujanga, Florence M.; Ssentongo, Grace Spencer; Ayugi, Gertrude; Akoba, Rashida; Biira, Saphina (In AIP Conference Proceedings, 2015)
For a long time, only one public university in Uganda had a department of physics. Several women graduated from this department, but not many showed much interest in pursuing higher degrees in physics. Currently, there are five public universities in Uganda with departments of physics, and there has been an increase in the number of female graduates in physics. At the same time, the number of women pursuing higher degrees in physics has increased, and the universities have registered an increase in female physics lecturers.